Inhibitory Control of Emotional Interference in Deaf Children: Evidence From Event-Related Potentials and Event-Related Spectral Perturbation Analysis - Chen, Qiong; Zhao, Junfeng; Gu, Huang; Li, Xiaoming (Frontiers in Psychiatry, 2022)
Background Impairment of interference control ability may reflect a more general deficit in executive functioning, and lead to an increase in internal-externalized problems such as impulsivity, which has been reported in deaf children. However, few researches have examined the neural mechanism of this impairment. Methods This study applied the electroencephalogram (EEG) technique to investigate the interference control ability in 31 deaf children and 28 hearing controls with emotional face-word stroop task. Results Results from behavioral task showed that deaf children exhibited lower accuracy compared to hearing controls. As for EEG analysis, reduced activation of ERP components in N1 and enhanced activation of ERP components in N450 have been found in deaf children. Besides, incongruent condition elicited larger N450 than congruent condition. Furthermore, for brain oscillation, alpha band (600–800 ms) revealed a reduced desynchronization in deaf children, while theta band (200–400 ms) revealed an enhanced synchronization in deaf children and incongruent condition, which were in line with ERP components. Conclusion The present findings seem to indicate that the deficit during emotional interference control ability among deaf children might be due to the impaired attention allocation ability and emotional cognitive monitoring function during emotional conflict detection process. Consequently, reduced N1 and enhanced N450 might be due to early attention impairment causing more effort of deaf children later in emotional cognitive monitoring.